Education, political affiliation and energy policy in the United States: A case of Tea Party exceptionalism?. (January 2017) - Mayer, Adam; Smith, E. Keith
Abstract: The Tea Party political movement began in the United States in 2009, driven by opposition to the presidency of Barack Obama. Prior research has shown that Tea Party Republicans differ from mainstream Republicans on a range of attitudes, such as belief in climate change and attitudes towards immigrants. However, it is unknown if Tea Party affiliation is consequential for energy policy. In this paper, we use an array of dependent variables related to a number of different energy policy options and find substantial differences between Tea Party Republicans and mainstream Republicans. In particular, Tea Party Republicans are much more supportive of increasing energy supply via fossil fuel extraction and less supportive of regulating power plants than mainstream Republicans. We also find that political affiliation is moderated by education, in which more educated Tea Party supporters are more resistant to energy regulation and more supportive of fossil fuels than Tea Party supporters with less education. Implications for future research and the energy policy regime in the United States are discussed.